Determination of chromium in water and wastewater - Suganty Kanapathy (2008)
The colorimetric analysis of chromium (Cr) in aqueous solution according to DPC method was investigated. The absorbance measurement can be taken at λ= 540 nm using a UV - VIS spectrophotometer at least 5 minutes after addition of required reagents to the Cr solution. The absorbance- concentration relationship obeyed the Beer Lambert Law at Cr concentration range 0-5 gg/mL. Analysis of unknown, river water, acid mine drainage (AMD) and wastewater samples using the colorimetric method gave Cr concentrations 0.211 - 1.815 μg/mL, 0.001 - 0.006 μg/mL (average = 0.007 f 0.002 gg/mL), 0.001 - 0.006 gg/mL (average = 0.004 ± 0.002 μg/mL) and 0.010 gg/mL, respectively. Comparatively, the Cr concentrations were 0.247 - 1.815 μg/mL, 0.082- 0.021 gg/mL (average= 0.034± 0.007 μg/mL), 0-0.048 μg/mL (average= 0.008 ± 0.001 gg/mL) and 0.123 μg/mL, respectively, when the analysis was carried out by atomic absorption spectrophotometry (AAS). Depending on the type of sample, the concentrations obtained according to DPC method were comparable or lower than those obtained by AAS method.